DATA FOR ASSESSMENT OF SENIOR SECONDARY SCHOOL BIOLOGY TEACHERS' AND STUDENTS' CONCEPT KNOWLEDGE OF COVID-19 IN OYO STATE, NIGERIA (2023)
The disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS – CoV-2) called COVID-19 has claimed a lot of lives across the world that the World Health Organization on 11 of March 2020, declared it a global pandemic. The Nigeria Centre for Disease Control (NCDC) has also been updating Nigerians about the pathogenic nature of the virus. Objectives This study assessed senior secondary school biology teachers’ and students’ concept knowledge of COVID-19 in Oyo State, and to show the type of relationship that existed between their concept knowledge. Methods A descriptive survey research design was adopted with two research questions and one research hypothesis. The sample size of the study included 620 Biology students (31 students per school) and 20 Biology teachers (1 teacher per school) from 20 senior secondary schools across 5 Local Government Areas in Oyo State. Two research instruments were used to collect data from respondents, these were Biology Teachers’ COVID-19 Concept Knowledge Test (r = 0.71), Biology Students’ COVID-19 Concept Knowledge Test (r = 0.79). The data were analyzed using descriptive statistics such as per centage (%), mean, and standard deviation; and inferential statistics such as Pearson Product-Moment Correlation Coefficient. Results It was revealed that senior secondary school biology teachers and students in Oyo State had high (63.15% and 61.17% respectively) levels of concept knowledge of COVID-19, however a moderate negative relationship that is not significant (r = -0.47; p>0.05) existed between them. Significance Biology teachers’ and students’ good concept knowledge of COVID-19 was an assurance that they were equipped with requisite concept knowledge of the disease, if there should be a resurgence. However, the not significant relationship between their concept knowledge of the disease, indicated a gap that needed to be filled.